Can blood flow restriction used during aerobic training enhance body composition in physique athletes? - Rolnick, N.; Schoenfeld, B. J. (Strength and Conditioning Journal, 2020)
Emerging evidence indicates low-load blood flow restriction (BFR) training is an effective strategy to increase muscular adaptations when performed during resistance training. Yet, it remains questionable as to whether combining BFR with traditional aerobic training can preserve or perhaps even potentiate hypertrophic adaptations. The purpose of this article is to provide an evidence-based review of current research on the topic and draw practical conclusions as to how BFR can be applied by physique athletes to optimize increases in muscle mass.